IMPLEMENTASI INOVASI PEMBELAJARAN IPA BERBASIS INKUIRI UNTUK MENUMBUHKANKEMBANGKAN KETERAMPILAN PROSES SAINS DAN SIKAP ILMIAH SISWA MELALUI KEGIATAN LESSON STUDY - Muslim, Muslim (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2011)
The purpose of this research is to improve the science process skills and scientific attitudes of students. In a lesson study activity, teachers of some Junior High Schools collaboratively developed a teaching learning process using the inquiry model for expansion concepts. The teaching learning process was carried out at one junior high schools in Bandung. The method used is the Classroom Action Research. Meanwhile, the instruments used in this research are observation formats involving teacher and student activities, science process skills and scientific attitudes of students, science process skill tests for students and lesson study observation sheets for observers. The objects of this research were the students class VII E 2010/2011 as many as 38 students who were enrolled in science learning. The results showed an increase in students' science process skills in science learning after using the inquiry learning model. The average of the normalized gain score of science process skills in the firts cycle is 0.67, in the second cycle is 0.49, and in the third cycle is 0,70. Based on observations in this research, the using of inquiry learning model can improve the science process skills of students. Besides, the scientific attitudes of students consisting of curiosity, cooperation, responsibility and discipline are well developed during the learning process.